A criação artística como espaço de pesquisa e experimentações em inteligência artificial - Cavalheiro, Mariane (2025)
This study investigates how artists, programmers, and multidisciplinary teams operate in creative spaces, combining artificial intelligence (AI) with artistic practice. The research addresses the challenges and opportunities that arise when various languages are experimentally explored in a laboratory setting, highlighting the importance of interdisciplinary collaboration, participatory communities, and experimental artistic practice. Computational thinking, for decision-making and problem-solving, promotes creativity, logical reasoning, and abstraction, creating new forms of artistic expression in their processes. This allows artists and programmers to collaborate across systems, using algorithms and computational models applied to artistic creation, exploring aesthetic patterns and complex interactions through open codes in multiple constructions. Artists like Alexandre Villares, and research laboratories for artistic creations such as those of researchers Lev Manovich and Fabrizio Poltronieri, who develop machine learning techniques in the production of image narratives and improvisation of interfaces between humans and non-humans, are the objectives of this research in seeking to integrate AI in a responsive and collaborative manner. Artificial intelligence (AI) embedded in interfaces and continuously trained becomes one of the actors in this process, being shaped by interactions and adversities, defining new structures of thought, mutually influencing the redefinition of creation processes, transforming as they are composed through social, moral, ethical, material, and discursive elements. In museums, AI acts as a cognitive agent, transforming the way we perceive and process this collective and collaborative construction process. By managing archives and memories, it establishes inclusions of historical repairs, bringing the practice and valuation of representativeness, transforming the cultural experience into a fairer one and offering training with different vocabularies as matrices, expanding and simulating artistic creation through computational models that can serve as a deepening of human sensitivity, replicating actions and different imaginative contexts